JEEA-FBBVA Lecture 2013: The New Empirical Economics of Management. Issue 4 (1st August 2014) - Bloom, Nicholas; Lemos, Renata; Sadun, Raffaella; Scur, Daniela; Van Reenen, John
Abstract: Over the last decade the World Management Survey (WMS) has collected firm-level management practices data across multiple sectors and countries. We developed the survey to try to explain the large and persistent total factor productivity (TFP) differences across firms and countries. This review paper discusses what has been learned empirically and theoretically from the WMS and other recent work on management practices. Our preliminary results suggest that about a quarter of cross-country and within-country TFP gaps can be accounted for by management practices. Management seems to matter both qualitatively and quantitatively for performance at the level of the firm and the nation. Competition, governance, human capital, and informational frictions help account for the variation in management. We make some suggestions for both policy and future research.